Atividade nematicida e indução de resistência em tomateiro Micro-Tom contra Meloidogyne spp. por frações proteicas de Pycnoporus sanguineus - Brito, Olivia Diulen Costa (2022)
The root-knot nematode (Meloidogyne sp.) is one of the limiting pathogens in the production of several crops of economic importance. The use of resistance inducers may be an option for the management of these parasites, since their control is very difficulty. The basidiomycete fungus Pycnoporus sanguineus has shown promising results for inducing resistance in several pathosystems, however, its effects on plantnematode interactions are poorly understood. Thus, the objective of this work was to obtain protein fractions from the aqueous extract of P. sanguineus by gel filtration chromatography (GFC) to induce resistance in MicroTom tomato plants against Meloidogyne spp. From the aqueous extract of basidiocarps, protein precipitation was performed with an increasing gradient of ethanol of 20%, 40%, 60%, 80% and 95%, which were individually centrifuged. Then, each protein precipitate (or ethanolic cut) was fractionated using CFG, and the protein peaks were separated and identified by molecular mass. Each protein precipitate as well as the isolated proteins were tested for nematicidal and nematostatic activity in vitro against M. incognita and M. javanica, evaluating motility and mortality. For resistance induction assays, MicroTom tomato seedlings had their root system immersed for 10 seconds in each treatment, and after three days of transplantation, seedlings were inoculated with 1,000 eggs of each nematode. The assay was carried out in a growth chamber with a photoperiod of 12 hours of light at 26 °C, and after 45 days the number of galls and number of eggs and number of second-stage juveniles (J2) in the root were evaluated, and the reproduction factor was calculated. Root samples were also collected in time for analysis of the defense enzymes peroxidase (POX), polyphenoloxidase (POL) and phenylalanine ammonia lyase (FAL) involved in the induction of resistance. Six protein fractions were obtained by CFG, identified as I, II, III, IV, V and VI, with molecular masses of 4.81; 47.98; 0.17; 25.78; 4.25 and 4 KDa respectively. In vitro, only the unfractionated aqueous extract and the ethanolic cuts 95% for M. javanica and 40%, 60%, 80% and 95% for M. incognita provided nematode mortality and immobility, while the protein fractions had no nematicide/nematostatic effects. In resistance induction tests, 60% ethanolic cut and fractions I to VI reduced the number of galls and the number of eggs + J2 per gram of root by up to 58% and 41%, respectively, for M. javanica, while for M. incognita these same treatments favored the infection with an increase of up to 59% in the number of galls. As for the enzymatic activity in the roots, protein fractions II and V for M. javanica increased four-folds POX activity, but reduced POL and did not influence FAL activity, while fraction VI for M. incognita had no effect on these three enzymes. Thus, P. sanguineus basidiocarps contain protein fractions capable of reducing M. javanica infection in MicroTom tomato plants, which can occur by inducing resistance involving the peroxidase enzyme.